C.2 - Bhaduri, Amit. (Delhi, 1984)
This work provides a theoretical frame work for an understanding of the economic structure of agricultural backwardness. It deals with the basic issues of exchange and surplus extrac tion, forced commerce in the market for agricultural produce, differentiation among indebted peasantry, the mainte nance of forced commerce through agri cultural backwardness, the method of usury, primitive accumulation through land alienation in backward agriculture and class relations and patterns of accumulation in backward agricultural societies. The study concludes with policies for agrarian change which are examined in a historical perspective.
Keywords: Market-Agricultural produce